Valgus knee motion during landing in high school female and male basketball players - Ford, K. R.; Myer, G. D.; Hewett, T. E. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this study was to utilize three-dimensional kinematic (motion) analysis to determine whether gender differences existed in knee valgus kinematics in high school basketball athletes when performing a landing maneuver. The hypothesis of this study was that female athletes would demonstrate greater valgus knee motion (ligament dominance) and greater side-to-side (leg dominance) differences in valgus knee angle at landing. These differences in valgus knee motion may be indicative of decreased dynamic knee joint control in female athletes. METHODS: Eighty-one high school basketball players, 47 female and 34 male, volunteered to participate in this study. Valgus knee motion and varus-valgus angles during a drop vertical jump (DVJ) were calculated for each subject. The DVJ maneuver consisted of dropping off of a box, landing and immediately performing a maximum vertical jump. The first landing phase was used for the analysis. RESULTS: Female athletes landed with greater total valgus knee motion and a greater maximum valgus knee angle than male athletes. Female athletes had significant differences between their dominant and nondominant side in maximum valgus knee angle. CONCLUSION: The absence of dynamic knee joint stability may be responsible for increased rates of knee injury in females but is not normally measured in athletes before participation. No method for accurate and practical screening and identification of athletes at increased risk of ACL injury is currently available to target those individuals that would benefit from neuromuscular training before sports participation. Prevention of female ACL injury from five times to equal the rate of males would allow tens of thousands of young females to avoid the potentially devastating effects of ACL injury on their athletic careers.